Capturing and Rendering Geometry Details for BTF-mapped Surfaces - Wang, Jinpeng; Tong, Xin; Snyder, John; Chen, Yanyun; Guo, Baining; Shum, Heung-Yeung (The Visual Computer, 2005)
Bidirectional texture functions, or BTFs, accurately model reflectance variation at a fine (meso-) scale as a function of lighting and viewing direction. BTFs also capture view-dependent visibility variation, also called masking or parallax, but only within surface contours. Mesostructure detail is neglected at silhouettes, so BTF-mapped objects retain the coarse shape of the underlying model. We augment BTF rendering to obtain approximate mesoscale silhouettes. Our new representation, the 4D mesostructure distance function (MDF), tabulates the displacement from a reference frame where a ray first intersects the mesoscale geometry beneath as a function of ray direction and ray position along that reference plane. Given an MDF, the mesostructure silhouette can be rendered with a per-pixel depth peeling process on graphics hardware, while shading and local parallax are handled by the BTF. Our approach allows real-time rendering, handles complex, non-height-field mesostructure, requires that no additional geometry be sent to the rasterizer other than the mesh triangles, is more compact than textured visibility representations used previously, and, for the first time, can be easily measured from physical samples. We also adapt the algorithm to capture detailed shadows cast both by and onto BTF-mapped surfaces. We demonstrate the efficiency of our algorithm on a variety of BTF data, including real data acquired using our BTF–MDF measurement system.